2000
DOI: 10.1038/sj.gene.6363711
|View full text |Cite
|
Sign up to set email alerts
|

A new type of genetic regulation of allogeneic response. A novel locus on mouse chromosome 4, Alan2 controls MLC reactivity to three different alloantigens: C57BL/10, BALB/c and CBA

Abstract: The intensity of the mixed lymphocyte response (MLR) depends on the genetic disparity between the donors of responding and stimulating cells. Differences in the major histocompatibility complex (MHC) and Mls1 antigens induce the strongest responses. However, even with comparable incompatibilities in MHC and Mls antigens, some strains of genetically defined mice respond remarkably better than other strains. Apparently other, so far undefined, genetic factors contribute to the magnitude of the MLR. The strain Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Some F 2 hybrids derived in cross between trypanotolerant African N'Dama ( Bos taurus ) and trypanosusceptible Kenya Boran ( Bos indicus ) cattle differed from both parents and contained less T. congolense parasites than any of them [37]. Similarly, mouse RC strain OcB-9 differs from both parental strains O20 and B10.O20 in response to alloantigens [38], several RC strains exhibit in some parameters higher susceptibility to Leishmania major than both parental strains BALB/c and STS [39], and analysis of gene expression from livers in chromosome substitution strains (background strain C57BL/6, donor strain A/J) revealed that only 438 out of 4209 expression QTLs were inside the parental range [40]. These observations are due to multiple gene-gene interactions of QTLs, which in new combinations of these genes in RC strains, F 2 hybrids or in chromosomal substitution strains can lead to appearance of new phenotypes that exceed their range in parental strains.…”
Section: Discussionmentioning
confidence: 98%
“…Some F 2 hybrids derived in cross between trypanotolerant African N'Dama ( Bos taurus ) and trypanosusceptible Kenya Boran ( Bos indicus ) cattle differed from both parents and contained less T. congolense parasites than any of them [37]. Similarly, mouse RC strain OcB-9 differs from both parental strains O20 and B10.O20 in response to alloantigens [38], several RC strains exhibit in some parameters higher susceptibility to Leishmania major than both parental strains BALB/c and STS [39], and analysis of gene expression from livers in chromosome substitution strains (background strain C57BL/6, donor strain A/J) revealed that only 438 out of 4209 expression QTLs were inside the parental range [40]. These observations are due to multiple gene-gene interactions of QTLs, which in new combinations of these genes in RC strains, F 2 hybrids or in chromosomal substitution strains can lead to appearance of new phenotypes that exceed their range in parental strains.…”
Section: Discussionmentioning
confidence: 98%
“…Our data indicates, that the observed differences are controlled by several non-linked loci. We have identified one of them as Alloantigen response 2 (Alan2 ) localized near the marker D4Mit72, which controls the response of OcB-9 to C57BL/10, BALB/c, CBA and perhaps also DBA/1 alloantigens [16]. Comparing the previously described genotypes of the OcB strains at this genetic region [45] revealed that B10.O20 derived segment in the region that contains the Alan2 locus is also present in the high responding strain OcB-16.…”
Section: Discussionmentioning
confidence: 99%
“…The first type includes the structural differences in major and minor antigens and their incompatibility between the stimulating cells and the responder. The second type is most likely based on polymorphism in gene(s) which code factor(s) participating in the T-cell receptor signal transduction or mediating costimulatory signals by antigen-presenting cells [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies found that some strong MLC-stimulations ( Mls ) antigens are coded by mouse Mtv (mammary tumor virus) [ 13 ]; later studies revealed a broad spectrum of additional minor human antigens [ 14 ]. Intensity of MLC-response to alloantigens is determined by two major factors—the genetic disparity between the responding and stimulating cells and the genetically defined intrinsic capacity of the responding cells to react to the stimulus [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%